Translanguaging: a coda to the code?. Issue 3 (2nd October 2019) - García, Ofelia
ABSTRACT: This coda considers how translanguaging discourse is manifested in classrooms. Li Wei and Lin open up spaces of possibility for translanguaging by questioning the order of language. In so doing, the school code assumes its appropriate place as a system of coloniality.